A real-world study to assess the effectiveness of itolizumab in patients with chronic plaque psoriasis - Anchala Parthasaradhi; Vinay Singh; S G Parasramani; Nishi Yadav; D S Krupashankar; Manish Soni; Rakesh Bansal (Wolters Kluwer Medknow Publications, 2017)
Background: While clinical trial data on the efficacy of itolizumab in the management of psoriasis is relatively well documented, data on the effectiveness of this humanized IgG1 monoclonal antibody in real-world settings is sparse. Aims: The current study assessed the effectiveness of itolizumab in real-world settings. Materials and Methods: This study assessed psoriasis area severity index (PASI), dermatology quality of life index (DLQI), safety, and tolerability data from a registry of itolizumab maintained by Syngene International, Bangalore. Registry data of 155 patients who were prescribed itolizumab at a dose of 1.6 mg/kg every 2 weeks for the first 12 weeks followed by 1.6 mg/kg every 4 weeks for up to 24 weeks for chronic plaque psoriasis. Results: In the study, 35.48% completed itolizumab for 12 weeks and 76.59% of these patients achieved PASI 75. Furthermore, 24.51% patients completed the full Itolizumab regimen for 24 weeks, of whom 92.01% patients achieved PASI 75. The mean percent change in DLQI scores at weeks 12 and 24 were 60.19 and 82.72, respectively. Adverse events and infusion reactions noted in the study were generally of mild to moderate severity. Conclusion: Itolizumab is a safe and effective option in treatment-compliant patients with chronic plaque psoriasis. Effects of putative compliance-modulators such as cost, route of administration, and delayed onset of action warrant further investigation.